An integrated simulation model for sand production prediction and sand control - Samsuri, Ariffin; Sim, S. H.; Tan, C. H. (2002)
The paper decribes the development of a computer package that can be used to predict sand production and select the optimum sand control. This package consists of two major parts. The first is simulation of perforation stability and onset of sand production. This is a coupled mechanical and fluid flow model. The main objectives of this model are predicting the onset of sand production, study the effect of perforation patternm, perforation density, phasing angle and 2-phase fluid (oil and water) production on the perforation cavity stability. The finite element method is used to develop this model. Among the assumptions made were that the reservoir rock surrounding the perforation cavity is assumed isothermal with its pores completely filled with fluid. The oil and water either in perforation cavity or in pores are considered totally immiscible. The deformation condition is considered nonlinear. The perforation boundary that is in contact with cement is assumed to be under no flow and displacement condition. In the events that sand production cannot be avoided, gravel packing is normally carried out to prevent the sand from entering the wellbore. This causes decline in well productivity, which is characterized by the additional pressure drop across the well. The productivity impairment is often aggravated by high-velocity flow. A finite-difference model is developed to evaluate the productivity of gravel-packed wells. This is the second part of the computer package and it represents an improved approach to the study of production impairment due to gravel-packing compared to the current practice of using the skin concept. In this work, the perforations are treated as cylinders and the annulus between the perforation and screen is filled with gravel.